HARD PATERNALISM, FAIRNESS AND CLINICAL RESEARCH: WHY NOT? - Edwards, Sarah J. L. (Bioethics, 2012)
Jansen and Wall suggest a new way of defending hard paternalism in clinical research. They argue that non-therapeutic research exposing people to more than minimal risk should be banned on egalitarian grounds: in preventing poor decision-makers from making bad decisions, we will promote equality of welfare. We argue that their proposal is flawed for four reasons. First, the idea of poor decision-makers is much more problematic than Jansen and Wall allow. Second, pace Jansen and Wall, it may be practicable for regulators to uncover the values that a potential research participant holds when agreeing to enter a research project, so their claim that we must ban such research projects for all if we are to ban them for poor decision-makers looks to be unmotivated. Third, there seem to be cases where the liberty to enter the sort of research project Jansen and Wall discuss is morally weighty, and arguably should outweigh concerns of egalitarian distribution. Fourth, banning certain types of research, which seem on the face of it to offer an unfavourable risk-benefit ratio, would have unwelcome consequences for all clinical research, which Jansen and Wall do not recognize.